43.6k views
1 vote
5 x [3 x (-2) - 10] i need the answer step by step please

User Josinalvo
by
4.8k points

2 Answers

3 votes

Answer: -80

First step is to calculate everything inside the brackets = [3× (-2) -10] = [(-6) - 10] = [(-16)] then we now multiply the number outside the brackets with the number inside the brackets which = 5[-16] = -80.

User Fijas
by
4.6k points
3 votes

Answer:

-80

Explanation:

5×(-6 - 10)

5×(-16)

-80

solve by using BODMAS rule

User Eric Koslow
by
4.5k points